“Identificación, evaluación y control de riesgos ergonómicos presentes en los procesos y puestos de trabajo que ocasionan daños en la salud de los trabajadores de Nevado – Ecuador. Diseño de un manual de ergonomía” - Matehu Gonzáles, Carlos (2011)
NEVADO-ECUADOR is a company dedicated to the production and export of flowers, it is located in the Mulalillo Parish, Salcedo Canton, Cotopaxi province, its processes and jobs involve all kinds of risks. To control them, it is convenient to start with an evaluation, this will allow determining which ones exceed the established safety limits, and only those that cause damage to the health of workers will be able to eliminate them.